2019
DOI: 10.1097/sla.0000000000002794
|View full text |Cite
|
Sign up to set email alerts
|

No Surgical Innovation Without Evaluation

Abstract: The intention of this article is to widen the practical use of IDEAL by clarifying the rationale for and practical details of the Recommendations. Additional research based on the experience of implementing these Recommendations is needed to further improve them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
126
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 292 publications
(129 citation statements)
references
References 52 publications
(37 reference statements)
2
126
1
Order By: Relevance
“…As doctors, we have a duty of care to our patients. In our view, this also extends to the rigorous evaluation of novel techniques, approaches, and devices [8]. This is important from the non-maleficence and safety perspective.…”
Section: Cisternostomy For Traumatic Brain Injury-rigorous Evaluationmentioning
confidence: 89%
See 1 more Smart Citation
“…As doctors, we have a duty of care to our patients. In our view, this also extends to the rigorous evaluation of novel techniques, approaches, and devices [8]. This is important from the non-maleficence and safety perspective.…”
Section: Cisternostomy For Traumatic Brain Injury-rigorous Evaluationmentioning
confidence: 89%
“…This raises questions around the statement that "waiver of consent was granted because the procedure was part of our written algorithm for the management of sTBI", given that the treatment algorithm would be different depending on who was the on-call neurosurgeon. This issue along with the fact that the published data on cisternostomy for TBI are very sparse indicates that the study should have happened prospectively in the context of a research protocol approved by an ethics committee [8].…”
Section: Cisternostomy For Traumatic Brain Injury-rigorous Evaluationmentioning
confidence: 99%
“…Numerous retrospective, prospective and case-controlled studies have indeed demonstrated the three steps of a robust evaluation of a new surgical procedure/ technology [1]: feasibility, safety and effectiveness of the robotic system. In addition, these studies resulted in equal or better specimen-oriented outcomes such as quality of TME, CRM, lymph node yield and many more.…”
mentioning
confidence: 99%
“…The IDEAL framework for new surgical procedures/ devices describes five stages of evaluation: idea, development, exploration, assessment and long-term study [1]. All this has been done for colorectal surgery since the introduction of the robot in 2000 without any clearly proven patient-related benefits.…”
mentioning
confidence: 99%
See 1 more Smart Citation